Incipient changes of lignin and substituted fatty acids under N addition in a Chinese forest soil. (February 2015) - Wu, Nana; Filley, Timothy R.; Bai, Edith; Han, Shijie; Jiang, Ping
Highlights: Soil total nitrogen was not influenced by nitrogen addition. Lignin phenols incipiently changed to increases of 5% only in degraded litter. Substituted fatty acids showed a small but significant increase (16%) in O horizon. Although recalcitrant compounds accumulated, SOC was not changed by N addition. Abstract: Elevated nitrogen (N) deposition has the potential to increase litter and soil carbon (C) storage by suppressing lignolytic activity, but reports of the response of forest floor and soil have shown inconsistent responses. We investigated organic carbon and nitrogen as well as lignin phenols and substituted fatty acids (SFA) in forest floor litter and organic horizons, and mineral soil profiles from a mixed broad-leaf Korean pine ( Pinus koraiensis ) forest, China after 6 years of N addition treatment at double the current N deposition rate. Total C and N were not influenced by experimental N deposition. However, incipient changes in extractable lignin phenol concentration were seen for degraded litter ( P = 0.100) exhibiting increases of about 5% while mineral soil, surface litter and O-horizon showed no change. The degree of lignin oxidation was not substantially influenced in any layer although a significant decrease in vanillyl lignin phenol oxidation was measured in the degraded litter under elevated N. Extractable substituted fatty acids in the forest floor and mineral soil horizons were also, essentially, insensitive to N addition with the minor exception of the O-horizon showing a small but significant (∼16%, P = 0.041) increase. Our results are consistent with one group of literature showing little change in overall soil and litter character under short term, 5–10 years, of N addition. Minor changes in molecular C dynamics, such as those observed for lignin phenols and substituted fatty acids could possibly be attributed to the suppression of microbial decay under N addition.